Vulnerability of Roof and Building Walls Under a Translating Tornado Like Vortex - Sabareesh, Geetha Rajasekharan; Matsui, Masahiro; Tamura, Yukio (Frontiers in Built Environment, 2019)
Exposure of a building to a tornado often proves fatal, resulting in massive destruction of property and structures. The effect of disasters can be minimized by understanding the nature of fluid-structure interactions when a tornado hits a building on its path. Earlier researchers have investigated extensively on building models exposed to stationary type vortex generated in a laboratory type tornado simulator; however studies using translating type vortex are few. In the present investigation, the external and internal pressures experienced by a building model are discussed based on experiments conducted using a translating tornado-like flow simulator at Tokyo Polytechnic University, Japan. The swirl ratio which characterizes the strength of vortices generated is kept constant. The investigation attempts to explore the opening locations which can result in higher internal pressures and net roof forces in building and the vulnerability of roof structures of buildings when exposed to tornado-like flow. The effect of translating speed on internal pressure fluctuations when compared to those of external pressures are investigated using aerodynamic admittance functions. Results indicate that there is an increased amount of internal pressure fluctuations at higher translating speeds.